Calcifying odontogenic cyst: Report of a case with unique features - Firoz Kamal; Manasa Deepthi; Vandana Raghunath (Wolters Kluwer Medknow Publications, 2019)
The calcifying odontogenic cyst (COC) was first categorized as a distinct entity by Gorlin et al. in 1962. It appears as a cyst lined by an ameloblastic epithelium, containing variable amounts of ghost cells and calcifications. Being a rare developmental odontogenic cyst, it accounts for about 1% of all odontogenic cysts (Shear, 1994) and represents about <6% of all odontogenic lesions. COC mimics other odontogenic cysts clinically as well as radiologically, and a definitive diagnosis can be made only by histological means. This article describes a case of COC, which presented as an anterior mandibular swelling in a 40-year-old female patient. Histologically, the presence of innumerable ghost cells with extensive areas of the partly calcifying eosinophilic matrix (suggestive of dentinoid) abutting the masses of ghost cells and the odontogenic epithelial component, set it apart from the usual histopathological findings.